Tanggung Jawab Polisi Sebagai Penagih Hutang - Alfons, Febriens Melfrens; Mustamu, Julista; Saija, Vica Jillyan Edsti (Pusat Studi Hukum dan Pemerintahan Fakultas Hukum Universitas Pattimura, 2024)
This research discusses the responsibilities of the police as debt collectors, where legally, in carrying out their duties, the police must comply with the disciplinary rules for police officers, one of which is that they are prohibited from being debt collectors or protecting people who have debts, as stated in Article 5 letter (h) of the Regulations. Government Number 2 of 2003 concerning Disciplinary Regulations for Members of the National Police of the Republic of Indonesia states that police are prohibited from being debt collectors or protecting people who have debts. However, in one example of the case in South Buru, namely the cooperative case, Lisa Fano, in her interview, once used police services as a source of threats. in collecting debts and one of the Palamaria families also often uses the services of the police as collectors and protectors. In this case the borrower does not use the services of a collector but uses the services of the police so that they feel that with the police, it will be easy to carry out the collection. The problem taken in this research is whether the police are responsible as debt collectors and what are the legal consequences if the police become debt collectors. The research method used in researching and discussing this problem is normative juridical. The legal materials used are primary, secondary and tertiary legal materials. Research results Based on the duties of the police as contained in Law number 2 of 2002, the police are not authorized to collect debts then the legal consequences for police who become debt collectors based on police regulation number 2 of 2003 can be subject to sanctions in the form of dishonorable dismissal, through The procedure is based on Regulation Number 2 of 2003, the legal consequences for the police are that they can be given heavy sanctions, namely dishonorable dismissal.